ASSESMENT OF CORRELATION, PATH ANALYSIS AND GENETIC VARIABILITY IN SESAME ( ARIABILITY IN SESAME (Sesamum indicum Sesamum indicum Sesamum indicum L.) ACCESSIONS CCESSIONS BASED ON MORPHOLOGICAL AND CAPSULE SHATTERING RELATED CHARACTERS - BEHERA, ANIL KUMAR; DASH, MANASI; KABI, MANDAKINI (The Bioscan, 2018)
The present research work was conducted with thirty five sesame accessions to study sixteen characters and the analysis of variance revealed highly significant differences among the genotypes for all sixteen characters. This indicates the presence of wide genetic variability among the genotypes. High values of PCV and GCV were noted for capsule number per plant, split of capsule before drying, opening of capsule before drying and seed yield per plot. A high heritability coupled with high genetic advance was found in capsules per plant, capsule split and open before drying and seed yield per plot. For most of the character pairs, genotypic correlations were higher than phenotypic correlations. Seed yield showed a highly significant and positive correlation with number of capsules per plant, branches per plant, capsule length, seed weight per capsule and number of seeds per capsule. The highest positive direct effect on seed yield was exhibited by capsules per plant followed by 1000- seed weight and capsule width at narrower side. The 35 genotypes formed eight conglomerates. The average inter-cluster distance varied from 299.29 (between cluster II and VI) to 1622.41(between cluster V and VII).